Mechanical and permeability properties of skeletal and sheet triply periodic minimal surface scaffolds in bone defect reconstruction - Alejandro Yánez; Alberto Cuadrado; Oscar Martel; María Paula Fiorucci; Sebastiaan Deviaene (Results in Engineering, 2024)
Triply periodic minimal surface (TPMS) structures have proven to be suitable for biomorphic scaffold designs orientated towards bone ingrowth applications. In this work, different types of gyroid Ti-6Al-4V scaffolds (skeletal-TPMS-based and sheet-TMPS-based) have been designed and fabricated by laser powder bed fusion for the purposes of analysing them and clarifying which type of scaffolds could be the best option to use in bone defect repair. The compression and bending tests conducted demonstrated that the skeletal gyroid scaffolds were flexible enough to promote bone healing. On the other hand, the sheet gyroid scaffolds tested might be too rigid to promote optimal bone growth inside the scaffold. The torsional properties were acceptable for most of the scaffolds. The values of Darcian permeability for all the tested scaffolds seemed to promote bone rather than cartilage ingrowth.